Post-flood outbreak of Xylosandrus crassiusculus and Diuncus corpulentus (Coleoptera: Curculionidae: Scolytinae: Xyleborini) on tree spices in Kerala - S R Hiremath, K D Prathapan, (Journal of Spices and Aromatic Crops, 2019)
Massive outbreak of Xylosandrus crassiusculus and Diuncus corpulentus (Coleopera: Curculionidae: Scolytinae: Xyleborini) on clove (Syzygium aromaticum) and nutmeg (Myristica fragrans) is reported from Kerala, India. Infestation results in drying up of branches and death of trees. This is the first report of the ambrosia beetle genera Xylosandrus and Diuncus on clove and nutmeg.